Growth of Pepper Plant (Piper nigrum Linn.) After Application of Organic Fertilizer Leaves of Gamal (Gliricidia sepium (Jacq) Kunth.) - Iir Purwanto; Zulfa Zakiah; Riza Linda (Jurnal Biologi Tropis, 2021)
Pepper (Piper nigrum Linn.) is the most traded spice commodity among other spices.ÃÂ  The problem with pepper farming in West Kalimantan is the lack of nutrient availability because plantation land is dominated by ultisol soils. Gamal leaf liquid organic diapers application is expected to increase the availability of nutrients in the growing media.ÃÂ  The aim of the study was to determine the nutrient content of the liquid organic diapers of gamal leaves, to see the effect, as well as the best concentration and time of application on the vegetative growth of pepper plants. The study was carried out for four months, namely from January to April 2020 at the Pepper Plantation of Tengon Village, using a factorial compeletely randomized design pattern consisting of 2 factors, the concentration such as 10%, 20%, 30%, 40% control and liquid organic fertilizer application time (every time week and every two weeks).ÃÂ  The results showed that liquid organic fertilizer of gamal leaves contained 12.7% C-organic., 0.27% N-Total., 47.03 C/N ratio., 0,25% P., and 0,29 K. The results of the research that giving Gamal leaf liquid organic fertilizer had a significant effect on shoot length, number of shoots and number of leaves of pepper plants, however, it did not significantly affect the time of emergence of pepper shoots. Liquid organic fertilizer concentration of 40% and time of application every week gave the best effect on shoot length (25.33 cm), number of shoots (4.33 shoots), and number of leaves (14.33 strands). ÃÂ It was concluded that the ÃÂ liquid organic diapers concentration treatment of gamal leaves had a significant effect on shoot length, number of shoots, and number of leaves of pepper plants but did not significantly affect the time of shoots emerging for pepper plants. ÃÂ The best poc concentration that increases pepper plant growth is 40% with every week application. ÃÂ It is recommended that further research can be carried out on the manufacture of ÃÂ liquid organic diapers of gamal leaves combined with animal waste on the growth of pepper plants, with application time of 2-3 times in one week.